Proactive university library book recommender system - Mekonnen, Tadesse Zewdu (Vaal University of Technology, 2021)
Too many options on the internet are the reason for the information overload problem to obtain relevant information. A recommender system is a technique that filters information from large sets of data and recommends the most relevant ones based on people‟s preferences. Collaborative and content-based techniques are the core techniques used to implement a recommender system. A combined use of both collaborative and content-based techniques called hybrid techniques provide relatively good recommendations by avoiding common problems arising from each technique. In this research, a proactive University Library Book Recommender System has been proposed in which hybrid filtering is used for enhanced and more accurate recommendations. The prototype designed was able to recommend the highest ten books for each user. We evaluated the accuracy of the results using Mean Absolute Error (MAE) and Root Mean Squared Error (RMSE). A measure value of 0.84904 MAE and 0.9579 RMSE found by our system shows that the combined use of both techniques gives an improved prediction accuracy for the University Library Book Recommender System.
M. Tech. (Department of Information Communication Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: University Library Book Recommender System; Collaborative and content-based techniques; Hybrid techniques; Hybrid filtering; Mean Absolute Error (MAE); Root Mean Squared Error (RMSE); Dissertations, Academic -- South Africa; Artificial intelligence -- Data processing; Electronic data processing; Self-organizing systems; Recommender systems (Information filtering)